Hubungan Antara Tingkat Nyeri Kanker Dengan Kualitas Hidup Pasien Kanker Yang Mengalami Cachexia Di Rumah Sakit Lavalette Malang - Novita, Rike Radian; Trigantara, Regista; Febriani, Reny Tri (Jurnal Keperawatan Muhammadiyah, 2025)
Introduction : The quality of life in cancer patients is caused by several factors, including complaints of pain, both due to the disease and the effects of treatment. Treatment given to cancer patients causes several effects such as nausea, loss of appetite, hair loss, body weakness and cachexia. Aim : The aim of this research is to find out whether there is a relationship between cancer pain and the quality of life of cancer patients who experience cachexia at Lavalette Hospital, Malang. Methode : The research design uses a correlational method with a retrospective approach. With a population of 250 respondents with a sample of 72 respondents. The sample technique used was purposive sampling. The patient's cancer pain was measured using the NRS scale. The patient's quality of life was measured using the WHOQoL-BREF questionnaire. The analysis used of the Spearman rho test analysis. Result : The results of the Spearman rho test analysis p value 0.758 when compared with a = 0.05, then Spearan rho 0.758 > 0.05. Conclution : There is no relationship between cancer pain and the quality of life of cancer patients who experience cachexia at Lavalette Hospital, Malang. This is influenced by several factors that can make coping strategies to reduce or reduce pain, thereby making the quality of life of cancer patients in the good category even though the pain scale felt is in the moderate category. Keywords: Cancer Pain, Quality of Life, Cachexia